Cloud learning technologies in the system of information and communication technologies for educational purposes - O. M. Turavinina (Academy of Cognitive and Natural Sciences, 2013)
Bykov understands information and communication technology as a computer-oriented component of pedagogical technology, reflecting some formalized model of a certain component of the content of training and methods of its presentation in the learning process, represented in this process by pedagogical software and involves the use of computers, computer-oriented learning tools and computer communication networks to solve didactic tasks or their fragments. The above interpretation requires some refinement since the list of ICT tools should be supplemented with cloud ICT tools, which are remote servers for storing and processing data of different types.